1974
DOI: 10.1111/j.1365-2141.1974.tb06771.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for the Lymphocytic Nature of Leukaemic Reticuloendotheliosis (Hairy‐Cell Leukaemia)

Abstract: Summary. A case of hairy‐cell leukaemia was studied by conventional cyto‐chemical, electronmicroscopic and immunofluorescence techniques. This condition is often known as leukaemic reticuloendotheliosis (LRE) but the nature of the proliferating cells has been in doubt. The accumulation of immunoglobulin‐synthesizing cells in the peripheral blood suggests that the involved cells are lymphocytes and no evidence for a reticular or endothelial origin of the LRE cell could be found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(13 citation statements)
references
References 23 publications
(1 reference statement)
2
11
0
Order By: Relevance
“…Similarly, both cytochemical (Mitus et al, 1961;Trubowitz et al, 1971;Yam, Li, and Finkel, 1972;Catovsky, Pettit, Galetto, Okos, and Galton, 1974b) and fine structural (Rubin, Douglas, Chessin, Glade, and Dameshek, 1969;Padilla and Soloff, 1971;Trubowitz et al, 1971;Ghadially and Skinnider, 1972;Katayama, Li, and Yam, 1972;Catovsky et at, 1974a, Daniel andFlandrin, 1974) studies have failed to define unequivocally the origin of the hairy cell, although Yam, Li, and Lam (1971) have demonstrated a specific tartrate-resistant acid phosphatase in the hairy cell, and a distinctive tubular inclusion has been demonstrated at the ultrastructural level (Katayama et al, 1972;Daniel and Flandrin, 1974;Catovsky et al, 1974a). Recently, Catovsky et al (1974b) and Haak, de Man, Hijmans, Knapp, and Speck (1974) have demonstrated immunoglobulin (Ig) on the surface of hairy cells, and, on the basis of these and other data, concluded that they are B cells. In the present paper we confirm and extend these findings with additional morphological and immunological data relating to a further four cases of leukaemic reticuloendotheliosis.…”
mentioning
confidence: 99%
“…Similarly, both cytochemical (Mitus et al, 1961;Trubowitz et al, 1971;Yam, Li, and Finkel, 1972;Catovsky, Pettit, Galetto, Okos, and Galton, 1974b) and fine structural (Rubin, Douglas, Chessin, Glade, and Dameshek, 1969;Padilla and Soloff, 1971;Trubowitz et al, 1971;Ghadially and Skinnider, 1972;Katayama, Li, and Yam, 1972;Catovsky et at, 1974a, Daniel andFlandrin, 1974) studies have failed to define unequivocally the origin of the hairy cell, although Yam, Li, and Lam (1971) have demonstrated a specific tartrate-resistant acid phosphatase in the hairy cell, and a distinctive tubular inclusion has been demonstrated at the ultrastructural level (Katayama et al, 1972;Daniel and Flandrin, 1974;Catovsky et al, 1974a). Recently, Catovsky et al (1974b) and Haak, de Man, Hijmans, Knapp, and Speck (1974) have demonstrated immunoglobulin (Ig) on the surface of hairy cells, and, on the basis of these and other data, concluded that they are B cells. In the present paper we confirm and extend these findings with additional morphological and immunological data relating to a further four cases of leukaemic reticuloendotheliosis.…”
mentioning
confidence: 99%
“…28 Although preferential expression of IgG3 has been documented, 29 multiple isotype expression on HCs has been reported previously. [30][31][32][33] It was initially suggested that this may be the result of passively adsorbed polyclonal immunoglobulin, since HCs have avid Fc receptors, [34][35][36] but rosetting techniques and the use of F(abЈ) 2 reagents have confirmed expression of multiple immunoglobulin isotypes in HCL. 37 An analysis of the clonal relatedness of the multiple isotypes expressed was made by generating heterohybridomas from HCs by fusion to a mouse myeloma cell line.…”
Section: Introductionmentioning
confidence: 99%
“…The most unusual and unique feature of HCL is expression of multiple IG isotypes on the tumour cell surface of 40% to over 80% HCL [77,80]. Although preferential expression of IgG3 has been documented [81], multiple Ig isotype expression on HCs has been reported for several decades [16,19,82,83]. It was found by southern blotting that individual hybridomas containing IGH rearrangements identical to the primary tumour secreted IgM, IgG or IgA, indicating that the tumour clone was undergoing CSR [84].…”
Section: Transposing the Pathogenetic Significance Of Ig Analysis In Hclmentioning
confidence: 99%